Is Fragmented Financing Bad for Your Health? - Steven D. Pizer; John A. Gardner (SAGE Publishing, 2011)
Americans finance health care through a variety of private insurance plans and public programs. This organizational fragmentation could threaten continuity of care and adversely affect outcomes. Using a large sample of veterans who were eligible for mixtures of Veterans Health Administration- and Medicare-financed care, we estimate a system of equations to account for simultaneity in the determination of financing configuration and the probability of hospitalization for an ambulatory care sensitive condition. We find that a change of one standard deviation in financing fragmentation increases the risk of an adverse outcome by one-fifth.